(untitled) (CIPEEX, 2022)
DOMESTIC VIOLENCE IS DEFINED BY THE WORLD HEALTH ORGANIZATION (WHO) AS THE INTENTIONAL USE OF FORCE OR POWER AGAINST ANOTHER PERSON OR AGAINST A GROUP OF PEOPLE, RESULTING IN INJURY OR HARM - BEING A VERY PRESENT ONE IN OUR COUNTRY. IN THIS CONTEXT, EPIDEMIOLOGICAL SITUATIONS COMMON AMONG MOST CASES CAN BE HIGHLIGHTED, SUCH AS THE AGE, ETHNICITY, AND SCHOOLING OF THE VICTIM, AS WELL AS THEIR RELATIONSHIP WITH THE AGGRESSOR AND THE FREQUENCY WITH WHICH THE CASES OF VIOLENCE OCCUR. OBJECTIVE: THUS, THIS STUDY AIMS TO DESCRIBE THE CHARACTERISTICS OF CASES OF DOMESTIC VIOLENCE REPORTED IN THE INFORMATION SYSTEM OF NOTIFICATION AND AGGRAVATIONS (SINAN) OF ANÁPOLIS, BETWEEN THE YEARS 2017 AND 2021. MATERIAL AND METHODS: THE WORK IS CONFIGURED AS AN EPIDEMIOLOGICAL, OBSERVATIONAL, DESCRIPTIVE, CROSS-SECTIONAL AND RETROSPECTIVE STUDY FOR THE ANALYSIS OF THE CLINICAL AND EPIDEMIOLOGICAL PROFILE OF VICTIMS OF DOMESTIC VIOLENCE BY ANALYZING THE COMPULSORY NOTIFICATION FORMS. RESULTS: THUS, IT WAS OBSERVED THAT THE PROFILE OF THE VICTIMS IN THE CITY OF ANÁPOLIS (GO), IS COMPOSED OF WOMEN AGED 18 TO 29 YEARS (38.0%), BROWN (69.8%), MARRIED OR IN CONSENSUAL UNION (38.9%), WITH INCOMPLETE ELEMENTARY EDUCATION (27.6%). IN MOST CASES THE VICTIM WAS NOT PREGNANT (82.5%), THE AGGRESSOR WAS MALE (79.3%), AND RECURRENCE WAS PRESENT IN 46.8% OF THE CASES. THE MAIN MEANS OF AGGRESSION IS BODILY FORCE (68.9%), AND ITS MAIN AGGRESSOR A PERSON WITH WHOM THE VICTIM MAINTAINS A MARITAL RELATIONSHIP, OR EX-MARITAL (46.7%), WITH THE HUSBAND BEING RESPONSIBLE FOR MOST CASES. IT IS ALSO NOTED THAT THE YEARS 2020 AND 2021 HAD A LOWER NUMBER OF CASES, SHOWING THE INFLUENCE OF THE COVID-19 PANDEMIC ON THE NUMBER OF NOTIFICATIONS, WHICH MASKED THE REAL NUMBER OF ASSAULTS THAT OCCURRED. CONCLUSION: THUS, THE PRACTICE OF REPORTING DOMESTIC VIOLENCE CASES IS AN IMPORTANT ATTITUDE FOR IMPROVING HEALTH CARE DELIVERY, AND CAN BE USED AS A SPECIFIC HEALTH INDICATOR BY MANAGERS AND HEALTH PROFESSIONALS.